2017
DOI: 10.1111/are.13532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhythmic temperature change on the growth, body composition and energy budget of hybrid grouper (Epinephelus lanceolatus ♂ × Epinephelus fuscoguttatus ♀)

Abstract: Effects of rhythmic temperature change on the growth, body composition and energy budget of hybrid grouper (Epinephelus lanceolatus ♂ 9 E. fuscoguttatus ♀) were investigated. Nine groups of fish received repeating cycles of low-temperature manipulation (22°C) for 1, 2 and 4 days followed by recovery temperature (28°C) for (3, 7 and 11 days), (6, 14 and 22 days) and (12, 28 and 44 days) respectively, designated as L1R3, L1R7, L1R11, L2R6, L2R14, L2R22, L4R12, L4R28 and L4R44 respectively. In the control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…These results indicated that L. acidophilus at 1 × 10 9 cfu/kg and probiotics cocktail at 3 × 10 9 cfu/kg were more efficient and the dosage might be optimal for the hybrid grouper to produce better growth performance in the present study. Interestingly, our unpublished data showed that dietary inclusion of C. butyricum CBG01 at 10 11 cfu/kg could significantly elevate the final weight and SGR of hybrid grouper (He, Tian, Feng, Dong & Wen, under review). Thus, the difference of the results in the study might derive from the probiotics species and dosage.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that L. acidophilus at 1 × 10 9 cfu/kg and probiotics cocktail at 3 × 10 9 cfu/kg were more efficient and the dosage might be optimal for the hybrid grouper to produce better growth performance in the present study. Interestingly, our unpublished data showed that dietary inclusion of C. butyricum CBG01 at 10 11 cfu/kg could significantly elevate the final weight and SGR of hybrid grouper (He, Tian, Feng, Dong & Wen, under review). Thus, the difference of the results in the study might derive from the probiotics species and dosage.…”
Section: Discussionmentioning
confidence: 99%